The impact of a yoga-based physical therapy group for individuals with traumatic brain injury: results from a pilot study. (2nd July 2020) - Krese, Kelly; Ingraham, Benjamin; O'Brien, Megan K.; Mummidisetty, Chaithanya K.; McNulty, Mary; Srdanovic, Nina; Kocherginsky, Masha; Ripley, David
ABSTRACT: Objective: To compare the impacts of yoga-based physical therapy versus a seated rest within the context of standard rehabilitation practice on sleep, heart rate variability (HRV), anxiety, and fatigue during acute traumatic brain injury (TBI) rehabilitation. Methods: Eleven individuals participated in this crossover study involving the following interventions in a randomized order: group yoga-based physical therapy (YPT), conventional physical therapy (CPT), and group seated rest in a relaxing environment (SR). HRV and self-reported anxiety and fatigue were measured immediately before and after each group, and sleep after each condition and at baseline. Data was analyzed using generalized linear mixed models with repeated measures. Results: The interaction between time and treatment was statistically significant ( p = .0203). For the SR treatment, wake after sleep onset (WASO) rate was reduced from 14.99 to 10.60 (IRR = 0.71; p = .006). Time and treatment were not found to be statistically significantly associated with any of the secondary outcomes. Conclusion: Yoga-based physical therapy is feasible and safe in the inpatient rehabilitation setting following TBI. Sleep quality improved following the addition of a one-hour seated rest in a relaxing environment to a standard rehabilitation daily schedule, suggesting that structured rest time may be beneficial to sleep hygiene during inpatient rehabilitation following TBI. ClinicalTrials.Gov Registration Number: NCT03701594